2011
DOI: 10.1177/1555343411415793
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Uncertainty Visualizations for a Dynamic Decision-Making Task

Abstract: Supporting complex decision making requires conveying relevant information characteristics or qualifiers. The authors tested transparency and numeric annotation for displaying uncertainty about object identity. Participants performed a "missile defense" game in which they decided whether to destroy moving objects (which were either threatening missiles or nonthreatening birds and planes) before they reached a city. Participants were provided with uncertain information about the objects' classifications. Uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These span from the simple approaches utilising colour, shapes and blinking, to the more complex glyphs, contour lines and animation. More recent studies [16,17] have concentrated on evaluating some of these and other visualisation approaches, at times with the aim of supplying general guidance for designers to use. Bisantz et al [16] in particular, identify transparency, brightness and saturation as useful techniques to convey uncertainty provided that background images and the overall task context are considered.…”
Section: Related Workmentioning
confidence: 99%
“…These span from the simple approaches utilising colour, shapes and blinking, to the more complex glyphs, contour lines and animation. More recent studies [16,17] have concentrated on evaluating some of these and other visualisation approaches, at times with the aim of supplying general guidance for designers to use. Bisantz et al [16] in particular, identify transparency, brightness and saturation as useful techniques to convey uncertainty provided that background images and the overall task context are considered.…”
Section: Related Workmentioning
confidence: 99%
“…However, the presentation of uncertainty information may provide additional benefits to dispatcher decision making. Uncertainty information has been shown to help improve decision making in contexts such as interpreting weather forecasts (Nadav-Greenberg & Joslyn, 2009) and assessing the identity of targets (Bisantz et al, 2011;Neyedli, Hollands, & Jamieson, 2011), resulting in both more accurate and faster decisions. But, users may not always use uncertainty information when it is available.…”
Section: Introductionmentioning
confidence: 99%
“…1. Various studies have shown that uncertainty visualizations significantly improve user performance [2], [3], [4], [5], enhance user awareness of the inherent prediction uncertainty [6], independent of the expertise level of the user [6], [7], and even when numerical information about the uncertainty is available as well [8].…”
mentioning
confidence: 99%